Effects of vitamin D supplementation on salivary cortisol and psychological health among postmenopausal women: A pilot quasi-experimental study - Syahdema, Muhammad F.; Siregar, Muhammad FG.; Nasution, Hiro HD.; Prabudi, Muhammad O.; Marpaung, Johny; Sukatendel, Khairani (Narra Sains Indonesia, 2025)
Menopause is a significant life transition often accompanied by mood disturbances, many of which are linked to cortisol levels and hypothalamic–pituitary–adrenal (HPA) axis dysregulation. Vitamin D deficiency is highly prevalent in postmenopausal women and shares overlapping adverse outcomes with menopausal symptoms. This study aimed to investigate the effect of vitamin D supplementation on salivary cortisol levels and psychological symptoms in postmenopausal women. This pilot study employed a quasi-experimental design, recruiting 32 postmenopausal women via consecutive sampling from the study population in Kwala Bekala Village, Medan Johor District. Participants were consecutively added into two groups, receiving either 1000 IU or 2000 IU of vitamin D daily for one month. Salivary cortisol levels and Depression, Anxiety, and Stress Scale (DASS) scores were measured before and after the intervention. The findings revealed that serum 25(OH)D levels increased significantly in both groups, with higher post-supplementation levels in the 2000 IU group than in the 1000 IU group (28.94±5.86 ng/mL vs 24.13±5.28 ng/mL, p=0.021). Salivary cortisol decreased in both groups, with a greater reduction observed in the 2000 IU group (median Δ=9.55 ng/mL vs mean Δ=4.92±4.29 ng/mL, p=0.032). Psychological symptoms measured by DASS scores also improved significantly, with the 2000 IU group showing a larger reduction (mean Δ=11.31±6.65 vs median Δ=3.5, p=0.022). Vitamin D supplementation at both 1000 IU and 2000 IU effectively reduced salivary cortisol and improved psychological symptoms in postmenopausal women. Due to differences in baseline characteristics, caution is warranted when inferring clear dose superiority.